IMPROVE STUDENT LEARNING RESULTS ON LEARNING PKN USING INQUIRY METHOD IN CLASS VI STUDENTS SDINPRES 2 UJUNA - Nuridaiman Amurun; Arif Firmasnyah (Education Journal, 2020)
This action research tries to improve the PKn learning outcomes of Grade VI students of SD Inpres 2 Ujuna. The subjects of this study were Grade VI students of SD Inpres 2 consisting of 37 students, consisting of 16 male students and 21 female students. Data was collected through teacher and student observation sheets and test results of the actions. The results of the study in the first cycle showed the classical absorption of students by 72.02% and the percentage of classical completeness of 54.05%. Whereas in the second cycle the percentage of classical absorption was obtained 82.07% and the percentage of classical learning completeness was 86.48%. Based on the percentage of completeness of learning outcomes in cycle I and cycle II, there has been a significant increase in classical absorption, an increase of 10.05% from the first cycle of 72.02% and the second cycle of 82.07%. Likewise in classical learning completeness of 32.435 from 54.05% in the first cycle and 86.48% in the second cycle. Based on these results it can be concluded that using the inquiry method can improve student learning outcomes of SD Inpres 2 Ujuna on Civics learning.